Utilization of Quiz Media in Increasing Students' Interest in Learning in Civics Subjects at SMKN 8 Palu - Sukmawati, Sukmawati; Jamaluddin, Jamaluddin; Alanur, Shofia Nurun; Chairil, Muhammad; Riski, Moh; Rata, Fildayanti; Magati, Hefinto; Tongenge, Miranda; Arif, Ahmad; Aprianto, Aprianto; Alfan, Alfan (CV. Rayyan Dwi Bharata, 2025)
This research aims to explore the use of quiz media as an interactive learning tool in increasing students' interest in learning. In the era of digitalization, the challenge of low interest in learning requires innovative solutions that involve technology as a learning tool. Media quizzes, which can be implemented online or offline, offer an evaluative approach that is not only interesting but also stimulates student activity. By providing a more interactive and enjoyable learning experience, this media functions as an evaluation and motivation tool. This research uses qualitative methods by collecting data from journals and literature related to the application of quiz learning media at SMKN 8 Palu. The research results show that the application of quiz media is effective in increasing students' interest in learning and understanding of learning material.